2010
DOI: 10.1016/j.pocean.2010.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Global integration of European tuna markets

Abstract: International audienceThis paper evaluates the degree of integration between the world market and the major European marketplaces of frozen and canned tuna through both vertical and horizontal price relationships. Spatial linkages are investigated horizontally in order to estimate the connection between the European market and the world-wide market on the primary stage of the value chain. One of the key results is the high level of market integration at the ex-vessel stage, and the price leadership of yellowfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…A number of recent studies have shown the strong globalization of tuna markets (Jeon et al 2008;Jiménez-Toribio et al 2010) and two separate market chains: purse-seine/cannery-grade and long-line/sashimigrade tuna (Miyake et al 2010). Each of these two distinct markets is highly integrated at the worldwide level across locations and species, making any regional change in catches important for the entire industry.…”
Section: Methods: a General Synthetic Inverse Demand System Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of recent studies have shown the strong globalization of tuna markets (Jeon et al 2008;Jiménez-Toribio et al 2010) and two separate market chains: purse-seine/cannery-grade and long-line/sashimigrade tuna (Miyake et al 2010). Each of these two distinct markets is highly integrated at the worldwide level across locations and species, making any regional change in catches important for the entire industry.…”
Section: Methods: a General Synthetic Inverse Demand System Approachmentioning
confidence: 99%
“…However, the data is not sufficiently comprehensive to evaluate the price response to the imports from all sources. Other authors utilized cointegration bivariate and multivariate tests through an error-correction model to show that prices of frozen tuna for canning co-moved in the longrun (Jeon et al 2008), that the law of one price holds between yellowfin and skipjack, and that Bangkok was clearly a market leader (weak exogeneity) (Jeon et al 2008;Jiménez-Toribio et al 2010). However, none of the past studies have directly measured the responsiveness of prices to changes in the global supply of cannery-grade tuna and its substitution within the canning industry.…”
Section: Methods: a General Synthetic Inverse Demand System Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…A quarter of the world's captured tunas ends up as sashimi (Jiménez-Toribio et al, 2010), which makes the control of product quality extremely important (Mateo et al, 2006), because only fish of excellent quality are used for its preparation.…”
mentioning
confidence: 99%